Ponadczasowość regulacji prawnych dotyczących niewypłacalności - Gil, Izabella (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The study describes the legal regulations concerning insolvency in the period of the Second Polish Republic. The political system of the Republic of Poland in the years 1926–1935 is described as authoritarian in order to distinguish it from the total fascist system. The difficult economic and financial situation of the Polish state during the post-partition period required state interference in introducing legal regulations ensuring protection of creditors, while taking into account the rights of debtors who became insolvent for no fault of their own. Bankruptcy became a society-wide problem, albeit of varying severity. The study describes legal regulations concerning insolvency, which are included both in the Ordinance of the President of the Republic of Poland of 24 October 1934, the Law on Settlement Proceedings (Journal of Laws of 1934, No. 93, item 836, with binding force from 1 January 1935), and in the Ordinance of the President of the Republic of Poland of 24 October 1934, the Bankruptcy Law (Journal of Laws of 1934, No. 93, item 834, with binding force from 1 January 1935). The above-mentioned legal acts contained regulations adjusted to the state of insolvency, which is the result of the debtor’s difficult economic and financial situation. The state of the debtor’s insolvency or the threat of insolvency determined whether it was possible to conduct a procedure in which the debtor entered into an arrangement with creditors or whether the debtor should be declared bankrupt. In the case of bankruptcy, a trustee appointed by the bankruptcy court managed the assets of the bankrupt, constituting the bankruptcy estate, and the bankrupt was deprived of the right to manage their assets. The main purpose of bankruptcy proceedings was to sell the assets included in the bankruptcy estate and to achieve equal satisfaction of creditors of the bankrupt debtor. The course of these proceedings was different and depended on whether it was possible to make an arrangement with the creditors or whether it was necessary to implement procedures related to the liquidation of the bankrupt debtor’s assets. Although both legal acts were enacted in the interwar period, they were in force until the entry into force of the Act of 28 February 2003, the Bankruptcy and Reorganization Law (Journal of Laws of 2003, No. 60, item 535), that is, for almost 60 years. Therefore, regardless of the changes in the political system of the Polish state, the insolvency regulations from the authoritarian period in the Second Republic remained in force for many decades. The timelessness of these regulations is confirmed by the fact that some of the legal regulations that were enacted in 1934 are still applied today, although they have been partially modified and adapted to the current economic situation. The entry into force on 1 January 2016 of the Law of 15 May 2018 on Restructuring Law (Journal of Laws of 2015, item 978) resulted in a return to the separation of legal regulations that can be implemented depending on the debtor’s difficult financial situation. The Restructuring Law currently regulates the proceedings enabling an insolvent debtor or a debtor at risk of insolvency to enter into an arrangement with creditors, the effects of an arrangement as well as the conduct of the rehabilitation proceedings. The purpose of the various types of restructuring proceedings is to avoid declaring bankruptcy. On the other hand, the Bankruptcy Law, similarly to the period of the Second Polish Republic, regulates the procedure, the main purpose of which is to achieve equal satisfaction of the creditors of the debtor in the bankruptcy to the highest possible extent, and only if rational considerations allow the debtor’s current enterprise to be retained.
Keywords: autorytaryzm; prawo upadłościowe; niewypłacalność